Case 3700: Diplodocus Marsh, 1878 (Dinosauria, Sauropoda): proposed designation of D. carnegii Hatcher, 1901 as the type species - Tschopp, Emanuel; Mateus, Octávio (Bulletin of Zoological Nomenclature, 2016)
The purpose of this application, under Articles 78.1 and 81.1 of the Code, is to replace Diplodocus longus Marsh, 1878 as the type species of the sauropod dinosaur genus Diplodocus by the much better represented D. carnegii Hatcher, 1901, due to the undiagnosable state of the holotype of D. longus (YPM 1920, a partial tail and a chevron). The holotype of D. carnegii, CM 84, is a well-preserved and mostly articulated specimen. Casts of it are on display in various museums around the world, and the species has generally been used as the main reference for studies of comparative anatomy or phylogeny of the genus. Both species are known from the Upper Jurassic Morrison Formation of the western United States. The genus Diplodocus is the basis for the family-level taxa Diplodocinae Marsh, 1884, Diplodocidae Marsh, 1884, Diplodocimorpha Marsh, 1884 (Calvo & Salgado, 1995) and Diplodocoidea Marsh, 1884 (Upchurch, 1995). It is also a specifier of at least 10 phylogenetic clades. With the replacement of D. longus by D. carnegii as type species, Diplodocus could be preserved as a taxonomic name with generally accepted content. Taxonomic stability of the entire clade Diplodocoidea, and the proposed definitions of several clades within Sauropoda, could be maintained.
Keywords: Nomenclature; taxonomy; Dinosauria; Sauropoda; Diplodocidae; Diplodocus; Diplodocus longus; Diplodocus carnegii; U.S.A.; Upper Jurassic Morrison Formation